Total synthesis of tetrahydroisoquinoline-based bioactive natural products laudanosine, romneine, glaucine, dicentrine, and their unnatural analogues isolaudanosine and isoromneine - Jangir, Ravi; Argade, Narshinha P. (Synthesis-Stuttgart, 2017)
Starting from suitably substituted homophthalic acids, total synthesis of titled alkaloids have been demonstrated in very good yields. The obtained natural products laudanosine and romneine were utilized to accomplish synthesis of two isoquinoline-based alkaloids glaucine and dicentrine. Base-induced selective generation of two different types of benzylic carbanions, their coupling reactions with 3,4-dimethoxybenzyl mesylate, and the regioselective iodination followed by intramolecular aryl-aryl coupling reactions to form the fused biaryl systems were the strategic steps.